PtrWRKY19, a novel WRKY transcription factor, contributes to the regulation of pith secondary wall formation in Populus trichocarpa - Yang, L.; Zhao, X.; Yang, F.; Fan, David; Jiang, Y.; Luo, K. (Nature Publishing Group, 2016)
WRKY proteins are one of the largest transcription factor families in higher plants and play diverse roles in various biological processes. Previous studies have shown that some WRKY members act as negative regulators of secondary cell wall formation in pith parenchyma cells. However, the regulatory mechanism of pith secondary wall formation in tree species remains largely unknown. In this study, PtrWRKY19 encoding a homolog of Arabidopsis WRKY12 was isolated from Populus trichocarpa. PtrWRKY19 was expressed in all tissues tested, with highest expression in stems, especially in pith. PtrWRKY19 was located in the nucleus and functioned as a transcriptional repressor. Ectopic expression of PtrWRKY19 in an atwrky12 mutant successfully rescued the phenotype in pith cell walls caused by the defect of AtWRKY12, suggesting that PtrWRKY19 had conserved functions for homologous AtWRKY12. Overexpression of PtrWRKY19 in poplar plants led to a significant increase in the number of pith parenchyma cells. qRT-PCR analysis showed that lignin biosynthesis-related genes were repressed in transgenic plants. In transcient reporter assays, PtrWRKY19 was identified to repress transcription from the PtoC4H2 promoter containing the conserved W-box elements. These results indicated that PtrWRKY19 may function as a negative regulator of pith secondary wall formation in poplar.